2002
DOI: 10.3168/jds.s0022-0302(02)74347-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supply of Metabolizable Protein on Splanchnic Fluxes of Nutrients and Hormones in Lactating Dairy Cows

Abstract: The effect of the supply of metabolizable protein on splanchnic fluxes of nutrients and hormones was measured in six catheterized late-lactation Holstein cows in a crossover design. Two isonitrogenous diets (16.3% CP), but differing in rumen protein degradability and estimated metabolizable protein (MP) supply (1654 g/ d, Lo-MP; 1930 g/d, Hi-MP) were fed, each over a 35-d experimental period. On d 34 or 35, net fluxes of nutrients and hormones across the portal-drained viscera, the liver, and total splanchnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
50
2
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 43 publications
15
50
2
1
Order By: Relevance
“…The butyrate fermentation following intake of grass with high sugar content might be part of the explanation for the typical decreasing milk production and milk fat production experienced when cows start to graze in the spring. In an experiment with intraruminal infusion of Figure 4 Portal-drained visceral (PDV) extraction of arterial urea-nitrogen in lactating dairy cows plotted against the arterial concentration of urea-N. Means from the following studies were used to establish the regression line (R 2 5 0.50) closed square (Reynolds et al, 2003); closed triangle up (Benson et al, 2002); closed triangle down (Blouin et al, 2002); closed diamond (Delgado-Elorduy et al, 2002a); closed hexagon (Delgado-Elorduy et al, 2002b); open square (Casse et al, 1994); open triangle down (Bach et al, 2000); open triangle up (Berthiaume et al, 2006); closed circle (Reynolds et al, 1988b); and open circle (Raggio et al, 2004). The mean PDV extraction of urea-N observed in the present study is indicated as an open diamond.…”
Section: Hourmentioning
confidence: 99%
“…The butyrate fermentation following intake of grass with high sugar content might be part of the explanation for the typical decreasing milk production and milk fat production experienced when cows start to graze in the spring. In an experiment with intraruminal infusion of Figure 4 Portal-drained visceral (PDV) extraction of arterial urea-nitrogen in lactating dairy cows plotted against the arterial concentration of urea-N. Means from the following studies were used to establish the regression line (R 2 5 0.50) closed square (Reynolds et al, 2003); closed triangle up (Benson et al, 2002); closed triangle down (Blouin et al, 2002); closed diamond (Delgado-Elorduy et al, 2002a); closed hexagon (Delgado-Elorduy et al, 2002b); open square (Casse et al, 1994); open triangle down (Bach et al, 2000); open triangle up (Berthiaume et al, 2006); closed circle (Reynolds et al, 1988b); and open circle (Raggio et al, 2004). The mean PDV extraction of urea-N observed in the present study is indicated as an open diamond.…”
Section: Hourmentioning
confidence: 99%
“…essential AA and 50 to 100% of the remainder is secreted into milk (Berthiaume et al 1999(Berthiaume et al , 2002Blouin et al 2002). However, the proportions are not static (Lapierre et al 2000).…”
mentioning
confidence: 99%
“…1. Leucine, Lys and Phe flux from small intestinal disappearance to milk protein, presented as a proportion of available flux (mesenteric appearance minus endogenous loss) and as a proportion (mol 100 mol -1 ) of the sum of essential AA fluxes [adapted from MacRae et al (1997), Berthiaume et al (2001) and unpublished data, Blouin et al (2002), and Ouellet et al (2002)]. …”
mentioning
confidence: 99%
“…The result in Experiment 2 confirmed this viewpoint. Some researchers also observed that dietary protein degradability did not affect the urea content in blood (Blouin et al, 2002;Reynal and Broderick, 2003) or milk (Rodriguez et al, 1997), whereas Davidson et al (2003) reported that MUN was affected significantly by the varying dietary RUP level. It has been suggested that a restriction in energy supply increases MUN (Kirchgessner et al, 1986).…”
Section: Resultsmentioning
confidence: 99%